2021
DOI: 10.1051/shsconf/20219101039
|View full text |Cite
|
Sign up to set email alerts
|

Business valuation in times of crisis

Abstract: Business valuation is very important and complex process, mainly in the current global situation. To determine the company value, we will base our calculations on an analysis of the internal environment of the company, which is affected by macroeconomic and microeconomic influences. The aim of this paper is to determine the value of a selected company using FCFF in an environment of negative and unplanned interventions in the economy. The main source for determining the value of the company is data obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The second method [39] is the discounted cash flow (DCF) method. The preference of the DFC method of valuation during the COVID pandemics is confirmed by [40] and is the most widely used method used in practice, as confirmed by [41].…”
Section: Forms Of Valuation Of Companies In Slovakiamentioning
confidence: 92%
“…The second method [39] is the discounted cash flow (DCF) method. The preference of the DFC method of valuation during the COVID pandemics is confirmed by [40] and is the most widely used method used in practice, as confirmed by [41].…”
Section: Forms Of Valuation Of Companies In Slovakiamentioning
confidence: 92%
“…They need to know the value of their company over time to understand how their business' performances can be interpreted on the long-run and how they are performing among their contenders. T. Krulicky, J. Horak and K. Skulcova (2021) write about the purpose of knowing the value of a business. According to them, decision-makers must be aware of the day-to-day value of their company to anticipate growth or development phases in order to lead it in the best direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors identified the role of innovation as a leading factor in economic growth, developed a conceptual apparatus, and identified the main cause-and-effect relationships. T. Krulický, et al [6] note that innovations should take into account the riskiness of decisions in conditions of high uncertainty, focus on the rapid achievement of goals, competitive advantage. Implementation of innovative projects is important for ensuring innovative development.…”
Section: Introductionmentioning
confidence: 99%